DNMT3A Mutations in Patients with Acute Myeloid Leukemia in South Brazil - Annelise Pezzi; Lauro Moraes; Vanessa Valim; Bruna Amorin; Gabriela Melchiades; Fernanda Oliveira; Maria Aparecida da Silva; Ursula Matte; Maria S. Pombo-de-Oliveira; Rosane Bittencourt; Liane Daudt; Lúcia Silla (Advances in Hematology)
Acute myeloid leukemia (AML) is a complex and heterogeneous hematopoietic tissue neoplasm. Several molecular markers have been described that help to classify AML patients into risk groups. DNA methyltransferase 3A (DNMT3A) gene mutations have been recently identified in about 22% of AML patients and associated with poor prognosis as an independent risk factor. Our aims were to determine the frequency of somatic mutations in the gene DNMT3A and major chromosomal translocations in a sample of patients with AML. We investigated in 82 samples of bone marrow from patients with AML for somatic mutations in DNMT3A gene by sequencing and sought major fusion transcripts by RT-PCR. We found mutations in the DNMT3A gene in 6 patients (8%); 3 were type R882H. We found fusion transcripts in 19 patients, namely, AML1/ETO (n=5; 6.1%), PML/RARα (n=12; 14.6%), MLL/AF9 (0; 0%), and CBFβ/MYH11 (n=2; 2.4%). The identification of recurrent mutations in the DNMT3A gene and their possible prognostic implications can be a valuable tool for making treatment decisions. This is the first study on the presence of somatic mutations of the DNMT3A gene in patients with AML in Brazil. The frequency of these mutations suggests a possible ethnogeographic variation.